2016
DOI: 10.1021/acs.molpharmaceut.6b00826
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Prodrugs of Ribavirin: Structure–Function Correlation as Inhibitors of Influenza Infectivity

Abstract: The requirement for new antiviral therapeutics is an ever present need. Particularly lacking are broad spectrum antivirals that have low toxicity. We develop such agents based on macromolecular prodrugs whereby both the polymer chain and the drug released from the polymer upon cell entry have antiviral effects. Specifically, macromolecular prodrugs were designed herein based on poly(methacrylic acid) and ribavirin. Structure-function parameter space was analyzed via the synthesis of 10 polymer compositions var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The nucleoside analogue ribavirin is a broad-spectrum antiviral drug and has been widely used for the treatment of viral hepatitis, lower respiratory tract infections, measles, and other viral infections (26,27). We found that ribavirin significantly inhibited CVA10, with in vitro inhibition and in vivo protection rates of 32% and 60%, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…The nucleoside analogue ribavirin is a broad-spectrum antiviral drug and has been widely used for the treatment of viral hepatitis, lower respiratory tract infections, measles, and other viral infections (26,27). We found that ribavirin significantly inhibited CVA10, with in vitro inhibition and in vivo protection rates of 32% and 60%, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Both cationic and anionic macromolecules were shown to be effective, including carrageenans, heparan sulfate, and sulfate derivatives of cellulose and lignin, dextran, chitosan, curdlan, xylan, and fucoidans and synthetic polymers such as sulfonated derivatives of poly(allylamine hydrochloride) (NSPAHs), dendrimers containing sulfonic groups, poly(sodium styrenesulfonate) and its copolymer with maleic acid, poly(methacrylic acid) functionalized with ribavirin, telomerized ω-acryloyl anionic surfactants and poly(ethylene glycol)-block-poly(3-(methacryloylamino)propyl trimethylammonium chloride) (PEG-b-PMAPTAC). These and many other polymers hamper a variety of pathogenic viruses, such as influenza A and B virus [ 14 , 15 ], herpesviruses [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], human immunodeficiency virus (HIV) [ 23 , 26 , 27 ], human metapneumovirus (hMPV) [ 28 ], and other viruses in in vitro and ex vivo models [ 29 , 30 , 31 , 32 , 33 , 34 ]. In vitro studies have shown that highly sulfated heparin, dextran sulfate, and suramin significantly inhibit ZIKV infection in Vero cells [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] This approach has successfully been applied by the Zelikin group to various RAFT‐polymerizable monomers carrying different types of drugs via this self‐immolative linker strategy. [ 42–50 ]…”
Section: Introductionmentioning
confidence: 99%
“…[41] This approach has successfully been applied by the Zelikin group to various RAFT-polymerizable monomers carrying different types of drugs via this selfimmolative linker strategy. [42][43][44][45][46][47][48][49][50] Additionally, self-immolative systems have also been developed in recent years to enable the reversible attachment of polymer chains to proteins. Besides reversible PEGylation by thiolthioester exchange with self-immolation by cyclization, [51] there are also approaches that use 1,6-elimination linkers, exploiting esterases, [52] thiol-disulfide exchange, [53] or azoreductases [54] as trigger mechanisms.…”
Section: Introductionmentioning
confidence: 99%